Subtle sabotage: endocrine disruption in wild populations - Cheek, Ann Oliver (Revista de Biología Tropical, 2006)
How important is endocrine disruption as a threat to wildlife populations? This review applies causal criteria to existing studies of wild populations of fish, amphibians, reptiles, birds, and mammals to answer three questions: (1) Have endocrine-mediated effects of contaminant exposure been documented? (2) Have individual adverse effects that could lead to population effects been documented? (3) Have population level effects been documented? In fish, the possibility of population level effects is inferred from impaired individual fertility. Substantial evidence directly links fertility impairment to endocrine disruption. In amphibians, population declines are occurring worldwide and causes may vary among regions, with contaminant-induced sexual disruption being one of many insults that stymie population growth. In reptiles, local populations of alligators have been dramatically reduced by direct toxicity and recovery has probably been slowed by sexual disruption, particularly feminization induced by chronic contaminant exposure. In contrast, heavily contaminated snapping turtles display feminized secondary sex characteristics, evidence of disrupted sexual development, but populations are densest at the most heavily contaminated site. In birds, population decline and recovery have been directly linked to p,p’-DDE-mediated eggshell thinning and subsequent banning of the parent compound DDT in the US and Europe. Regional populations of predatory birds still suffer chick mortality related to PCB and DDT burdens, but no causal link with endocrine-mediated processes has been demonstrated. In mammals, contaminant- induced hormonal derangements in seals and polar bears have been documented, but no clear evidence links endocrine effects to population declines. Although endocrine disruption will rarely be the sole cause of failing recruitment or decreased abundance, it may subtly sabotage sexual development, sex ratio, and metabolic compensation for environmental stress. Endocrine disruption is unlikely to extirpate a species over its entire range, but in combination with other stressors such as habitat loss, over-harvesting, and global climate change, may contribute to local extinctions. Rev. Biol. Trop. 54(Suppl. 1): 1-19. Epub 2006 Sept. 30.